Categorização de comportamentos adaptativos de pessoas que vivem com HIV/AIDS - Lavezzo, Fernanda (2024)
Introduction: adherence to highly active antiretroviral treatment (HAART) can be an important barrier to adequate health care. Objective: to characterize people living with HIV/AIDS (PLWHA) and exhibit adaptive behaviors in response to treatment, and to correlate the control variables for these behaviors. Material and Method: this is a cross-sectional descriptive study. Outpatients on antiretroviral treatment who had, for more than 12 months, an undetectable viral load and CD4 ≥ 500 cells/mm3 were evaluated. For data collection, the following instruments were used: sociodemographic questionnaire, Semi-structured interview, WHOQOL-bref, Problem coping scale (EMEP), Questionnaire to assess adherence to antiretroviral treatment (CEAT-HIV), Social support scale for people living with HIV/AIDS, Self-Efficacy expectancy scale to follow antiretroviral prescription and Cross-sectional symptom scale (ETS). Qualitative and quantitative analysis of the data collected was carried out with descriptive statistics and statistical tests (p ≤ 0,05). Results: male predominance, low education and family income of 2 to 4 minimum wages. The majority demonstrated good or strict adherence to treatment, identified two or more sources of social support, and did not present severe psychiatric symptoms. There was a good expectation of self-efficacy regarding antiretroviral treatment, adequate perception of general quality of life and social support and satisfaction with health. The main way of coping obtained was focused on the problem. Positive correlations were found between coping strategy, quality of life, social support, adherence to antiretroviral treatment and expected self-efficacy. And negative differences between age, time since diagnosis, coping strategy and quality of life. Comparative analyzes were also carried out between mental health and the other variables mentioned above. The majority reported having no difficulty with drug treatment and listed motivation related to quality of life, social support and spirituality. Among the main tips offered by participants, persistence in treatment, the search for adequate information and social support stood out. Conclusions: adherence to antiretroviral treatment consists of a collaborative and co-responsible process in health care. Given the drug's effectiveness, reducing the daily number of pills and adverse effects provides health, survival and quality of life for PLWHA. Furthermore, psychological adaptation to HIV/AIDS associated with satisfaction with available social support and the presence of religiosity encourage adherence and maintenance of treatment, promote healthy lifestyles and active health management, and strengthen PLWHA's ability to cope with a chronic and stigmatizing disease.